Incentive modes and reducing emissions from deforestation and degradation: who can benefit most?. (15th August 2016) - Sheng, Jichuan; Cao, Jie; Han, Xiao; Miao, Zhuang
Abstract: An incentive mechanism is key to succeed the investments in Reducing Emissions from Deforestation and Degradation programs. However, the diversification of determinants makes it difficult to establish one mode to best incentive stakeholders. This paper compares various incentive modes in benefiting stakeholders by simulating dynamic game models. It analyzes the profit-making of developers and landholders based on four incentive modes. The modes are preferential tax for developers, incentive of carbon offsets for developers, investment incentive for developers, and incentive of reducing emissions for landholders. This paper compares the effects of incentive modes on benefit distribution of stakeholders and contributes to a new dynamic game framework. The results show that: (i) the effects of incentives of carbon offsets for developers and incentives of reducing emissions for landholders are almost same for the stakeholders; (ii) a preferential tax can only make developers unilaterally benefit, and will not change landholder welfare; (iii) investment incentives for developers can make landholders' profits be increased, while the effects of incentives on developers' profits are uncertain. Finally, the numerical simulation is used to verify these hypotheses. The core implication is that for the design of REDD+ incentives, the government should combine various incentive modes to fulfill different objectives in policy making. Highlights: Dynamic game models are used to compare four incentive modes of REDD+ programs. Fairest incentives are carbon offsets for developers and incentives for landholders. Preferential tax benefit developers unilaterally. Investment incentives for developers can increase landholders' profits. Government should combine incentives strategically.